VD_FINDINFO AI 166/13 - 261/2014 vom 17. Juni 2014 - VD Tribunal cantonal (2014)
NOUVELLE DEMANDE, AGGRAVATION DE L'ATTEINTE À LA SANTÉ, EXPERTISE MÉDICALE | 28 LAI, 4 LAI, 17 LPGA, 6 LPGA, 8 LPGA, 87 al. 3 RAI